A multidimensional framework for disaster recovery: Longitudinal qualitative evidence from Puerto Rican households. (August 2021) - Sou, Gemma; Shaw, Duncan; Aponte-Gonzalez, Felix
Highlights: Societal conditions (Disaster support; public services; markets; employment and public financial assistance) shape recovery. Households leverage their assets and recovery priorities to mitigate and/or adapt to changes in societal conditions. Societal enablers and household enablers vary over time, and interact to shape a households' capacity to recover. Recovery must expand to include needs that do not directly adapt to, reduce or avoid the impacts of hazards. Qualitative longitudinal methodologies uncover how households unequally recover over time. Abstract: Research on household disaster recovery has principally applied quantitative methods to explain, in a correlative way, the speeds at which households recover. Yet there are limited explanatory models of household recovery. This study adopts a qualitative, longitudinal methodology to develop a model of how and why household recovery pathways and speeds are heterogenous. Data was collected over five field visits to Puerto Rico during the first year after Hurricane Maria in 2017. Households mobilise their agency to leverage their assets and recovery priorities to mitigate and/or adapt to four major societal conditions (disaster support; public services; markets; employment and public financial assistance). These societal conditions and household characteristics act as enablers and barriers, which vary over time, and interact to shape households' capacity to recover. The paper also proposes a new definition of disaster recovery, which reflects households' pursuit of recovery needs that do not directly adapt to, reduce or avoid the impacts from disasters.